FATF as international law institute - Кудас, І. Б. (Problems of legality, 2013)
The article is devoted to the history of creation, analysis of the legal bases of activity, forms of decision-making, control over their implementation, measures of impact on the national banking system «of the Task force on financial measures in the sphere of money laundering». In article also addressed the question of the modern status of international bodies in the system of subjects of international law.